Padrões de qualidade de vida e fatores associados em pessoas diagnosticadas com hanseníase entre 2001 e 2014, nos municípios de Vitória da Conquista e Tremedal, Bahia. - Rosa, Priscila do Nascimento (2017)
Leprosy is a chronic, neglected disease of compulsory notification and considered of great importance for public health, due to the high number of cases and its high incapacitating potential that limits the individual in the performance of his routine activities, including reduction of the capacity to Work, restriction of social participation, and psychological problems that presumably influence their quality of life (QOL). The general objective of this study is to characterize quality of life standards and associated sociodemographic and clinical factors in people diagnosed with leprosy between 2001 and 2014 in the city of Vitória da Conquista and Tremedal, Bahia. This is a cross-sectional population-based study, with descriptive and analytical analysis. Data collection through the World Health Organization Quality of Life (WHOQOL) instrument in its bref and senior version (OLD), proposed by the World Health Organization- WHO, and the Quality of Life Index in Dermatology (DLQI), as well as sociodemographic and clinical data. The data were analyzed using the Stata / SE 11.0 statistical program, with univariate analysis done using simple frequency measures and the central tendency and dispersion measurements, the bivariate analysis performed using the non-parametric Mann-Whitney, Kruskal -Wallis and chi-square test. In both municipalities, there was a predominance of women of brown color, married, in the economically active age group and with low schooling, the majority in Vitória da Conquista resided in the urban zone and in Tremedal all were residents in the rural area. The results of the QOL resembled the two municipalities. According to the WHOQOL-bref, the QOL of people diagnosed with leprosy was considered good in all domains, the highest score found was in the social relations domain and the lowest score in the environment domain. The overall QOL score in the elderly (WHOQOL-OLD) was considered good, where the death and dying facet had a higher score (75) in Vitória da Conquista and in Tremedal the highest score (68.75) was equal in the facets sensory functioning, social participation And death and dying. The QOL results of the DLQI instrument demonstrated that the highest percentages of people were classified without QOL impairment in both municipalities. However, it is concluded that there is a relation of leprosy with precarious socioeconomic conditions, in agreement with the profile that the literature addresses and that it is necessary to implement interventions that take into account not only the clinical aspects, but also the QOL of people with Leprosy, since the disease has physical, psychic and social impact.